Adaptation as a premise for perceptual-based multimedia communications. (23rd May 2005) - Ghinea, Gheorghita; Thomas, Johnson P.; Magoulas, George D.; Heravi, Saeed
The vision of a new generation of network communication architectures, which deliver a Quality of Service based on intelligent decisions about the interactions that typically take place in a multimedia scenario, encourages researchers to look at novel ways of matching user-level requirements with parameters characterising underlying network performance. In this paper, we suggest an integrated architecture that makes use of the objective-technical information provided by the designer and the Quality of Perception metric for intelligent decision making in the construction of user-centred adaptable communication protocols. This approach, based on the Analytic Hierarchy Process, incorporates not only classical Quality of Service considerations, but indeed, user preferences as well, and opens the possibility for the suggested protocols to dynamically adapt based on a changing operating environment. Results show that the proposed approach does provide an enhanced user multimedia experience when compared with legacy communication protocols.